La efectividad de los juegos cooperativos, como recurso alternativo para modificar la agresión proactiva y reactiva en adolescentes de La Casa de la Niñez Nº 2 - Saltos Almeida, Andrea Susana (2014)
Research on "The effectiveness of cooperative games, as an alternative resource to modify proactive and reactive in adolescents of the House of Children No. 2 aggression "was held in the months of October and November 2013. The research sample conformed 10 adolescents between the institution and experience life in street, who according the proposal made in the research design, cooperative games were developed by combining games designed by the author and other orrespondientes games to the literature review, and pretending to modify the levels of reactive and proactive aggression participants.